Women and the Lambe-Lambe Theater: an account of the diffusion in Santa Catarina (Móin-Móin Magazine - Studies in the Art of Puppetry, 2020)
This article presents the relationship between women and the Lambe-lambe Theater, specifically the creation of this specific language by Denise dos Santos and Ismine Lima in Bahia and the diffusion realized by several women in the state of Santa Catarina. It presents a brief contextualization about the creation of the Lambe-lambe Theater in Salvador and then focuses on the identification of the women creators in Santa Catarina, recognizing the elements that motivated the diffusion of the language and effervescence in the state. Also presents the first Lambe-lambe Theater course offered by a public institution in the Initial Training Course in Animation Theater - FINTA by IFSC - Florianópolis Campus, in 2018.
Keywords: Lambe-lambe Theater. Women. Santa Catarina.